Skeleton Creek / 1. - Carman, Patrick (Skeleton Creek, 2009)
Although housebound following an eerie accident, teenaged Ryan continues to investigate the strange occurrences in his hometown of Skeleton Creek, recording his findings in a journal and viewing email video clips sent by fellow detective Sarah.